2008
DOI: 10.1016/j.jacc.2007.11.035
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant and Antiplatelet Therapy Use in 426 Patients With Atrial Fibrillation Undergoing Percutaneous Coronary Intervention and Stent Implantation

Abstract: Patients with AF undergoing PCI with stenting represent a high-risk population because of age, comorbidities, and presence of stroke risk factors. These patients have a high mortality and MACE rate, which is reduced by anticoagulation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
135
4
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(147 citation statements)
references
References 24 publications
1
135
4
7
Order By: Relevance
“…LEKAMI PRZECIWZAKRZEPOWYMI I LEKAMI PRZECIWPŁYTKOWYMI Przebyty zawał serca stwierdza się u około 15% pacjentów z AF uczestniczących we współczesnych próbach klinicznych [513] i rejestrach [514][515][516]. U 5-15% pacjentów z AF w którymś momencie ich życia będzie konieczne stentowanie.…”
Section: Skojarzona Terapia Doustnymiunclassified
“…LEKAMI PRZECIWZAKRZEPOWYMI I LEKAMI PRZECIWPŁYTKOWYMI Przebyty zawał serca stwierdza się u około 15% pacjentów z AF uczestniczących we współczesnych próbach klinicznych [513] i rejestrach [514][515][516]. U 5-15% pacjentów z AF w którymś momencie ich życia będzie konieczne stentowanie.…”
Section: Skojarzona Terapia Doustnymiunclassified
“…Approximately 15% of AF patients in contemporary trials 513 and registries 514 -516 have a history of myocardial infarction. Between 5 -15% of AF patients will require stenting at some point in their lives.…”
Section: Combination Therapy With Oral Anticoagulants and Antiplateletsmentioning
confidence: 99%
“…From 625 initial citations, 16 eligible studies including a total of 9185 patients were identified in the present meta‐analysis,4, 5, 6, 7, 12, 14, 15, 19, 20, 21, 22, 23, 24, 25, 26, 27 with 5680 patients in the triple therapy group and 3505 in the dual therapy group (Figure 1). …”
Section: Resultsmentioning
confidence: 99%
“…Finally, 12 studies were identified in the DAPT subgroup,4, 5, 6, 7, 19, 20, 21, 22, 23, 24, 25, 26 with the other 4 studies included in the OAC/C subgroup 12, 14, 15, 27…”
Section: Resultsmentioning
confidence: 99%